Efficacy of generic highly Active antiretroviral therapy In HIV-1 infected individuals in Nigeria (2015)
CD4 T lymphocyte and plasma HIV RNA parameters have been used to monitor disease progression, and predict clinical course in HIV infection. Initial evaluation of these parameters was conducted in the western countries where accessible ARVs, circulating HIV subtypes and mode of transmission are different from the situation in Nigeria. This study appraised these parameters, and efficacy of generic ARVs. Consenting 106 HIV infected ARV naïve patients were enrolled. CD4 Tlymphocyte and plasma HIV RNA levels were determined at interval for 24 months. Ninety eight (92.5%) of the patients who completed the follow up in strict adherence to therapy guideline were included in the analysis. Baseline median CD4 T lymphocyte increased from 114 (Range: 6–330) to highest 357 (Range: 15–1036) cells/μL at 18 months of therapy, while baseline median plasma viral RNA declined from 4.6 (Range: 2.6–6.0) Log10 copies/mL to undetectable level within three months of therapy. Significant CD4 T-cell restoration and plasma viral RNA decline in the study population demonstrate efficacy of the generic HAART. The importance of combined use of both parameters for evaluation of immunologic and virologic responses to ART was confirmed.